Chapter Valori e tecniche nell'assetto dei licenziamenti emergente dopo la sentenza della Corte Costituzionale n. 194 del 2018 - MAIO, Valerio (Studi e saggi, 2022)
This paper try to compose a taxonomy of constitutional values with reference to dismissal. Moving from the key decision of the Constitutional Court no. 194 of 2018, the author investigates the relevance of the founding value "work" compared and balanced with the other antagonistic values: the "enterprise" and the "employability". The author claims that "legal certainty", nay the predictability and computability of rights, is not a tyrant value, but a principle necessary for good law, and not only for the economy. Finally, this paper analyzes the important consequences of sentence no. 194 cit. in the field of regulatory technique and about application problems.